PHRASEOLOGICAL UNITS IN EDUCATIONAL POLICY: CHALLENGES IN TEACHING NATIVE IDIOMS - Mahmudjonova Rayxona; Olimova Dilafruz; Anvarova Zaxro; Dustmatova Xonzodabegim; Abdurasulova Zaxro (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article explores challenges in teaching phraseological units, especially native idioms, in language education. Using a qualitative approach, it identifies learner difficulties, curriculum gaps, and teaching issues, and suggests context-based methods to improve idiomatic competence.